Effectiveness of Artificial Reproducion Acipenser Gueldenstaedtii - Nikonorova, Hanna; Kireeva, Irina (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The Russian sturgeon is vanishing species. A Russian sturgeon is also known as “Diamond Sturgeon“ or “Tsar Fish“ because of its majestic size and look. River Dam projects have affected almost all spawning ground of this species. It is estimated that the wild population of the Russian Sturgeon has reduced by 90% in just three generations of the species. Interest in replenishing wild stocks with hatchery-reared fish has created a need for an accurate methodological process of fertilization of both fish raised in aquaculture systems and fish in the wild. The caviar of the Russian sturgeon is one of the most sought after, and the flesh of the fish is also in demand always making poaching of the fish more frequent. The objective of this study was monitoring main indexes for Russian sturgeon in a period of spawning. Was holding a characterization of the main indicators of females of Russian sturgeon, a correlation between the main indicators.